2022
DOI: 10.18502/kls.v7i2.10388
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Nurses' Knowledge and Practices Regarding Triage

Abstract: Triage is the most important step in the emergency room. Triage is useful for ensuring that every patient gets rapid, precise, responsive and accurate treatment according to their condition based on ABCDE (airway, breathing, circulation, disability, environment) priorities. For this reason, it is necessary for nurses to be competent in the knowledge and skills related to triage. This study aimed to determine the association between knowledge and the implementation of triage by nurses at the Siloam Hospital in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
0
2
Order By: Relevance
“…Comparison of results with previous findings shows conformity with (Hardianto et al, 2023) research supporting the relationship between nurse response time and accuracy of triage assessments. However, these results contradict a study conducted by (Lea et al, 2022), which found no significant association between nurses' knowledge and the accuracy of triage assessments. These findings can be explained by considering the role of training and education in strengthening nurses' knowledge as well as the importance of efficient assessment in responding to patient needs.…”
Section: Discussioncontrasting
confidence: 99%
“…Comparison of results with previous findings shows conformity with (Hardianto et al, 2023) research supporting the relationship between nurse response time and accuracy of triage assessments. However, these results contradict a study conducted by (Lea et al, 2022), which found no significant association between nurses' knowledge and the accuracy of triage assessments. These findings can be explained by considering the role of training and education in strengthening nurses' knowledge as well as the importance of efficient assessment in responding to patient needs.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, those findings concurred with Moirangthem (2019) who found that more than half of nurses had average level of knowledge about triage (31) , this can be supported by Pouy et al (2019) who revealed that most of the nurses did not have enough knowledge related to triage (32) . On the contrary side, the current study did not match the findings of Ina Lea etal (2022), who stated that more than half of nurses had good knowledge of triage, nearly half had moderate knowledge, and none had poor knowledge (33) . This can be clarified by pointing out that the nurses in that study received triage training and they had participated in at least one training, and some had participated in more than one training course.…”
Section: Figure (3): Correlation Between Total Nurses' Knowledge and ...contrasting
confidence: 99%